2020
DOI: 10.1525/elementa.424
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of factors controlling PM2.5 variability across the South Korean Peninsula during KORUS-AQ

Abstract: deployed instrumented aircraft and ground-based measurements to elucidate causes of poor air quality related to high ozone and aerosol concentrations in South Korea. This work synthesizes data pertaining to aerosols (specifically, particulate matter with aerodynamic diameters <2.5 micrometers, PM 2.5) and conditions leading to violations of South Korean air quality standards (24-hr mean PM 2.5 < 35 µg m-3). PM 2.5 variability from AirKorea monitors across South Korea is evaluated. Detailed data from the Seoul … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 97 publications
3
53
0
Order By: Relevance
“…In Part 1 (Jordan et al, 2021) of this two-part work, hyperspectral aerosol extinction (σ ext ) measurements from a field campaign in South Korea were used to examine the usefulness of characterizing the spectra with second-order polynomial rather than traditional linear fits (i.e., power laws with negative slopes known as Ångström exponents) to the logarithmically transformed spectra. It was found that secondorder polynomials provided better fits to the data and that using the two-coefficient mapping approach introduced by Schuster et al (2006) holds promise for providing more detailed information on ambient aerosol size distributions than can be obtained from single Ångström exponents alone.…”
Section: Introductionmentioning
confidence: 99%
“…In Part 1 (Jordan et al, 2021) of this two-part work, hyperspectral aerosol extinction (σ ext ) measurements from a field campaign in South Korea were used to examine the usefulness of characterizing the spectra with second-order polynomial rather than traditional linear fits (i.e., power laws with negative slopes known as Ångström exponents) to the logarithmically transformed spectra. It was found that secondorder polynomials provided better fits to the data and that using the two-coefficient mapping approach introduced by Schuster et al (2006) holds promise for providing more detailed information on ambient aerosol size distributions than can be obtained from single Ångström exponents alone.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the vertical profiles of nanoparticles and their evolution during the EOF2 case suggest that the entrainment of nanoparticles from the upper layer into the shallow and humid boundary layer and the increase in their size via hygroscopic growth, consequently contributing to increase in PM2.5 mass concentration. In fact, the PM2.5 mass concentration increased at Aewol, up to 63 g m -3 (Table 2), as well as Seoul during the EOF2 case (Jordan et al, 2020). Recently, it was suggested that pollutants were carried from the upstream areas in the upper layer by westerly winds, remained above the nocturnal boundary layer, and entrained into the PBL during the day; this led to a high PM10 concentration at the surface (Lee et al, 2019).…”
Section: Chemical Evolution Coupled With Boundary Layer Expansionmentioning
confidence: 96%
“…We considered the deliquescence relative humidity (DRH) of inorganic salts, such as NH4NO3 and (NH4)2SO4, as a crucial factor for the rapid particle growth, because the SIA was the predominant constituent of PM2.5 during the KORUS-AQ period (Jordan et al, 2020). In the morning, the burst of particle>3.5 nm above 4 was found near the surface and just above the inversion layer with RH below the DRHs of both (NH4)2SO4 and NH4NO3 (Fig.…”
Section: Chemical Evolution Coupled With Boundary Layer Expansionmentioning
confidence: 99%
See 2 more Smart Citations